2008
DOI: 10.1007/s11483-008-9089-0
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior of Food Emulsions Mixed with Saliva: Effect of Oil Content, Salivary Protein Content, and Saliva Type

Abstract: In this paper, we studied the effect of saliva on the rheological properties of β-lactoglobulin-and lysozyme-stabilized emulsions, prepared at pH=6.7 in relation to variation of emulsions-and saliva-related parameters. The effect of oil-volume fraction (2.5% w/w to 10% w/w), salivary protein concentration (0.1 to 0.8 mg ml −1 ), and the use of both stimulated and unstimulated saliva was investigated. Viscosity and storage modulus were measured before (η emul and G′ emul , respectively) and after addition of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 67 publications
0
19
0
1
Order By: Relevance
“…Saliva properties differ as a function of the collection method (Proctor, ; Stokes & Davies, ). Many studies demonstrated distinct results (e.g., rheology, tribology) when using stimulated versus unstimulated saliva (Prinz et al, ; Silletti et al, ). In addition, the difference of salivary stimulation is magnified in the elderly.…”
Section: Changes In Quantity and Quality Of Bulk Saliva On Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva properties differ as a function of the collection method (Proctor, ; Stokes & Davies, ). Many studies demonstrated distinct results (e.g., rheology, tribology) when using stimulated versus unstimulated saliva (Prinz et al, ; Silletti et al, ). In addition, the difference of salivary stimulation is magnified in the elderly.…”
Section: Changes In Quantity and Quality Of Bulk Saliva On Agingmentioning
confidence: 99%
“…Stimulated saliva contains lower quantities of protein (e.g., glycosylated mucin) and has a lower viscosity than that of the unstimulated counterpart. Many studies demonstrated differences in rheological and tribological properties between these two types of saliva (Prinz, de Wijk, & Huntjens, 2007;Silletti, Vingerhoeds, van Aken, & Norde, 2008).…”
mentioning
confidence: 99%
“…The proteomic study revealed over 1050 diverse kinds of proteins in saliva. One of the constituents of the saliva, which is mucins consist of highly glycosylated particles (Silletti et al, 2008). More than a few protein organizations such as MUC5B networks increase the complexity of the saliva structures.…”
Section: Discussionmentioning
confidence: 99%
“…The process of emulsion breakdown begins in the mouth where salivary mucins and shear between the tongue and palate cause extensive flocculation and coalescence [8]. In the stomach there is some enzymatic hydrolysis of the surface proteins which may lead to coalescence as well as possible flocculation induced by the change in pH [9].…”
Section: Introductionmentioning
confidence: 99%